Fabricação digital em contextos educacionais: Interlocuções teóricas e práticas sobre o currículo - Alves, Leonardo França de Morais (2024)
The research aims to reflect on the integration of digital manufacturing technologies into the curriculum of non-formal education, considering the specificities and latent contents of this set of techniques, its historical development, and social significance. It addresses the introduction of digital manufacturing technologies from the perspective of Maker education, reflecting on and contextualizing its ideas and proposals, especially regarding the role of making and manufacturing in education. To this end, it discusses the history and social and political imaginaries surrounding work automation. The research adopts a qualitative research approach, utilizing narrative methodology anchored in the curriculum experiences of the researcher[1]educator within the context of the Technologies and Arts Program and the Curumim Program at SESC São Paulo, as well as theoretical analysis of ideas surrounding digital manufacturing in the curriculum. Therefore, it discusses the concepts of technique and technology according to Álvaro Vieira Pinto, from an epistemological perspective, and addresses the history of industrial work automation in its confluence with pedagogical and childhood ideas. The research presents challenges and contributions to understanding the integration of new technologies into the curriculum, especially those of digital manufacturing, considering the curricular construction of critical and emancipatory education, where manufacturing presents itself as an epistemic, ethical, and political exercise of knowing, manipulating the world, and transforming it